Health Disparities in COVID-19: Addressing the Role of Social Determinants of Health in Immune System Dysfunction to Turn the Tide - Baumer, Yvonne; Farmer, Nicole; Premeaux, Thomas A.; Wallen, Gwenyth R.; Powell-Wiley, Tiffany M. (Frontiers in Public Health, 2020)
It is evident that health disparities exist during the SARS-CoV-2 (COVID-19) pandemic. Underlying reasons for COVID-19 health disparities are multi-factorial. However, social determinants, including those regarding socioeconomic status, social inequalities, health behaviors, and stress, could have implications on these disparities. Exposure to one or more of these social determinants is associated with heightened inflammatory responses, particularly increases in the cytokine interleukin-6, as well as immune system dysfunction. Thus, an amplified effect during SARS-CoV-2 infection could occur, potentially resulting in vulnerable patients experiencing an intensified cytokine storm due to a hyperactive and dysfunctional immune response. Further understanding how social determinants play a mechanistic role in COVID-19 disparities could potentially help reduce health disparities overall and in future pandemics.